A Proposal for a Coherentist-Constitutivist Account of Normativity - Cheng, Yixue (Anna) (Stance: an international undergraduate philosophy journal, 2020)
We operate under norms of evaluating actions as good and bad, right and wrong, or reasonable and unreasonable. What justifies the authority of these norms? Christine Korsgaard takes the constitutivist position and argues that self-constitution, as the standard for what constitutes action, is the source of normativity. David Enoch argues that it is impossible for any constitutivist model to justify normative standards, and that realism is the best solution. In this paper, I demonstrate that the best solution to the tensions Enoch raises is not realism, but an original coherentist-constitutivist model of normativity rooted in Korsgaardian constitutivism.